Application of a fluorescence in situ hybridization (FISH) method to study green tides in the Yellow Sea. (20th September 2015) - Zhang, Qing-Chun; Liu, Qing; Yu, Ren-Cheng; Kang, Zhen-Jun; Guo, Wei; Ding, Yue-Min; Chen, Jian-Hua; Wang, Yun-Feng; Li, Yan; Yan, Tian; Zhou, Ming-Jiang
Abstract: Massive green tides of Ulva prolifera have been recorded consecutively since 2007 in the Yellow Sea (YS). It has been proposed that the floating green algae in the YS are originally from the culture rafts of Porphyra yezoensis in the Subei Shoal. However, there is still much debate about this, mainly due to the difficulty in rapid and accurate identification of U. prolifera . In this study, a developed fluorescence in situ hybridization (FISH) method was adopted to identify U. prolifera and assess its relative abundance in the green algal community. Using this method, several processes related to the formation of green tides were studied, including: (1) variation of the relative abundance of U. prolifera in the green algal community attached to Porphyra rafts in the Subei Shoal; (2) contribution of the microscopic propagules in seawater to the U. prolifera population attached to the rafts; and (3) variation of the proportion of U. prolifera in the floating green algae in the YS. U. prolifera were detected in the green algae attached to Porphyra rafts from March to May 2012, where its relative abundance increased rapidly from 10% at the end of April to 40–60% in mid-May. Microscopic propagules of U. prolifera, which could be detected from seawater and sediment, contributed significantly to the dramatic increase of the attached U. prolifera on the Porphyra rafts. After the attached green algae were removed from the rafts, U. prolifera rapidly demonstrated dominance in the floating green algal community, and the proportion of U. prolifera increased gradually from south to north. Our conceptual model is that the germination of U. prolifera microscopic propagules on Porphyra rafts promotes the proliferation of attached U. prolifera on the rafts, which release more microscopic propagules into seawater and sediments after they became mature. This positive feedback enhances the dominance of U. prolifera in the attached green algal community in late May, which leads to the formation of green tides after the attached plants are removed from the rafts during Porphyra harvest. The proportion of U. prolifera then increases rapidly in the resuspended and floating green algal community due to its unique structure, making it the most dominant species of floating green algae. The application of the FISH method clearly depicted the early development of green tides in the Subei Shoal and greatly helped to solidify the proposed linkage between Porphyra culture rafts and the formation of green tides in the YS. Graphical abstract: Highlights: A fluorescence in situ hybridization (FISH) method was adopted to study green tides. We found bloom-forming Ulva prolifera on Porphyra rafts with the FISH method. U. prolifera became dominant in green algal community attached on rafts in May. Microscopic propagules in seawater promoted proliferation of attached U. prolifera . Proportion of U. prolifera increased further in floating green algae in Yellow Sea.